(untitled) (Research, Society and Development, 2021)
The resistance mechanism due to the production of broad-spectrum beta-lactamases (ESBL) has been increasingly common in public health, both in hospital and in community. The objective of this study was to analyze the cases of ESBL in enterobacteria isolated from outpatients urine cultures. This is a quantitative, descriptive cross-sectional study, retrospective documentary type. Data were collected from the uroculture records of community patients treated at a private laboratory of Analysis, located in Montes Claros, Minas Gerais, from October 2016 to September 2017. There were 6,248 uroculture reports analyzed, wich 15.7% (n=984) were positive. Among the positive ones, 79.4% (n=781) were enterobacteria and 4.5% of these (n=35) are producing ESBL. Among ESBL producers, the most prevalent species were Escherichia coli (68.6%/n=24), and Klebsiella pneumoniae 25.7%/n=9). Analyzing ESBL antimicrobial resistance profile, it appears that 100% are resistant to all cephalosporins. There was also a significant percentage of strains resistant to antibiotics with beta-lactamases inhibitors (31.4%), quinolones (71.4%) and sulfamethoxazole/timetoprime (71.4%). The Klebsiella pneumoniae isolates showed a significant relationship with 3.76 greater chance (p <0.0008) of being ESBL producers. This study shows bacterial resistance regarding the production of ESBL presents in community pathogens, outside the hospital environment.